(untitled) (المجلة العراقية للعلوم الاقتصادية, 2024)
The research aims to draw attention to the role of the Iraqi banking sector in managing the climate change risk profile according to Iraq’s sustainable Vision 2030 and its accession to the Paris Climate Agreement under Law (31) for the year 2020 ، Through the research contribution to setting the main pillars of the guiding principles for sustainable financing by the international proposals of the International Green Financial System Network (Network for greening the financial system-NGFS). In addition to addressing the sustainable initiatives announced by the Central Bank of Iraq, the research will focus on the renewable energy initiative that was unique to the Central Bank of Iraq to achieve carbon neutrality while proposing guidelines for sustainable financing to respond to carbon reefs ، In addition to developing disclosure in the banking sector in a so-called disclosure of carbon footprint reports through indicators for these reports ، The research reached many conclusions, most notably the absence of a guide for sustainable financing in the Iraqi banking sector, despite the existence of initiatives to achieve sustainability that were limited to individual instruction. In addition to the recommendations made by the research, which centred on proposing reports to follow up the application of the guiding principles of sustainable financing with the issuance of carbon footprint reports for each bank.